2002
DOI: 10.1076/clin.16.3.280.13849
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Attention Measures in Postconcussion Syndrome

Abstract: Neuropsychological evaluation may be of particular relevance in the detection of subtle cognitive impairments after mild traumatic brain injury (MTBI), including the subgroup of MTBI patients with a persistent postconcussion syndrome (PCS). Attention measures may be the most sensitive indicators of dysfunction associated with MTBI; however, previous studies have typically relied on the analysis of overall group differences, which may not reflect the diagnostic accuracy of attention measures when applied to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 14 publications
9
57
2
1
Order By: Relevance
“…The rAC is actively implicated in cognitive control domains (56) such as selective attention processing and working memory (48,49). These are cognitive domains that have previously been found to be dysfunctional in PCS (57,58). Consistent with the functional role of the rAC, we found that rAC WM volume changes in patients with MTBI correlated significantly with scores on the CVLT, a test of verbal memory, learning, and encoding, as well as with scores on the PASAT, a test of attention.…”
Section: Discussionsupporting
confidence: 70%
“…The rAC is actively implicated in cognitive control domains (56) such as selective attention processing and working memory (48,49). These are cognitive domains that have previously been found to be dysfunctional in PCS (57,58). Consistent with the functional role of the rAC, we found that rAC WM volume changes in patients with MTBI correlated significantly with scores on the CVLT, a test of verbal memory, learning, and encoding, as well as with scores on the PASAT, a test of attention.…”
Section: Discussionsupporting
confidence: 70%
“…However, mDSM-IV (COG) criteria diagnosed fewer control participants with PCS, and there were higher cognitive failures and more cognitive RPQ items reported by those with mTBI than those without. This suggests that cognitive deficit could be an important distinguishing factor for PCS between those with concussion and healthy non brain injured populations [42,80]. Subjective criteria may not be specific enough to diagnose PCS after mTBI.…”
Section: Pcs In Populations With and Without Mtbi 20mentioning
confidence: 99%
“…With Trail Making tests that require complex attention and cognitive flexibility, completion times increase with increasing severity of head injury (Dikmen et al, 1995) and are associated with diffuse axonal injury (Felmingham et al, 2004), but they may not be sufficiently sensitive measure in mild brain injury (Cicerone & Azulay, 2002). Scores from both Trails A and Trails B contributed to the prediction of degree of independent living of moderate and severe TBI patients, with shorter completion times associated with greater likelihood of independent living (Acker & Davis, 1989).…”
Section: General Description Reliability Data Validity Datamentioning
confidence: 99%
“…In addition to differentiating TBI patients from controls, performance on the SDMT test differentiated between early versus late recovery (Bate et al, 2001) and was sensitive to the effects of diffuse axonal injury (Felmingham, Baguley, & Green, 2004), and predicted changes in the daily functioning 5 years after TBI (Hammond, Hart, Bushnik, Corrigan, & Sasser, 2004). TBI patients have slower completion times on the subtests of the Stroop, although they do not consistently show disproportionate difficulty with the interference condition (Ponsford & Kinsella, 1992;Felmingham et al, 2004) and some have questioned the sensitivity of the Stroop Interference test as a diagnostic tool in mild TBI (Cicerone & Azulay, 2002). Measures of auditory attention span, as the Digits Forward test, tend to be more sensitive to left versus right hemisphere damage and performance on this test correlates with the number of concussions or brain injuries (Matser, Kessels, Lezak, Jordan, & Troost, 1999).…”
Section: General Description Reliability Data Validity Datamentioning
confidence: 99%
See 1 more Smart Citation